Mass production of functional human pancreatic β‐cells: why and how?. (September 2016) - Scharfmann, R.; Didiesheim, M.; Richards, P.; Chandra, V.; Oshima, M.; Albagli, O.
Abstract : Diabetes (either type 1 or type 2) is due to insufficient functional β‐cell mass. Research has, therefore, aimed to discover new ways to maintain or increase either β‐cell mass or function. For this purpose, rodents have mainly been used as model systems and a large number of discoveries have been made. Meanwhile, although we have learned that rodent models represent powerful systems to model β‐cell development, function and destruction, we realize that there are limitations when attempting to transfer the data to what is occurring in humans. Indeed, while human β‐cells share many similarities with rodent β‐cells, they also differ on a number of important parameters. In this context, developing ways to study human β‐cell development, function and death represents an important challenge. This review will describe recent data on the development and use of convenient sources of human β‐cells that should be useful tools to discover new ways to modulate functional β‐cell mass in humans.